Changes in Youth’s Experiences of Child Maltreatment Across Developmental Periods in the LONGSCAN consortium - Villodas, Miguel T. (2012)
OBJECTIVE: The present study applied person-centered data analytic techniques to identify groups of youth with allegations for combinations of maltreatment types during preschool, early and late childhood. METHOD: Latent Class Analyses were conducted using officially reported child maltreatment data for five types of maltreatment (i.e., failure-to-provide and lack-of-supervision neglect, and physical, sexual and emotional abuse) from 788 youth in a large prospective study during preschool, early, and late childhood. RESULTS: Three similar classes were identified during preschool and early childhood, characterized by no maltreatment allegations, allegations for neglect and emotional maltreatment, and allegations for all maltreatment types. During late childhood, four classes were identified characterized by no maltreatment allegations, mixed patterns of maltreatment allegations, physical and emotional abuse allegations, and allegations for all maltreatment types. Youth in maltreated classes were more likely to be re-victimized during subsequent developmental periods, often by similar maltreatment combinations. Youth in maltreated classes characterized by physically violent maltreatment types had higher Externalizing and Total behavior problems at each age. CONCLUSIONS: These findings confirm the vulnerability of maltreated youth to re-victimization, particularly by similar combinations of maltreatment. They also indicate that youth’s susceptibilities to specific forms of maltreatment may vary across developmental periods.